Optimizing the Modulation Efficiency of Silicon-on-Insulator-Based Optical Phase Modulator - Mardiana, Bidin; Sahbudin, Saari; Menon, P.S; Haroon, Hazura; Hanim , Abdul Razak; N., Arsad; H., Abdullah (American Scientific Publishers, 2013)
This paper reports on the optimization of the modulation efficiency of an SOI-based optical phase modulator using Taguchi method. The fabrication and characterization of the device was virtually executed using SILVACO TCAD simulator. The modulation efficiency of the device was optimized using signal-to-noise ratio (SNR) of ‘smaller-the-better.’ Four control factors were selected namely the rib dimension of the optical waveguide, applied voltage, doping concentration and the doping position. In addition, four noise factors were also included to achieve robustness of the proposed device design which is the annealing temperatures for both the p-doped and n-doped wells as well as the phosphorous and boron implant energy for both the p-doped and n-doped wells. It was discovered that the bias voltage is the most dominant factor in determining the modulation efficiency. Confirmation tests on the predicted control and noise factor combination revealed that the modulation efficiency improved by 97.6% (0.0103 V·cm) as compared to the nominal device parameters. In short, Taguchi method paves the way for a cheap and time-efficient method to achieve device optimization prior to the actual fabrication.